Democracy and communications : an analysis and assessment of the public participation programme of the Constitutional Assembly - Skjelten, Synnøve (Department of Political Studies, 2015)
This thesis analyses the Public Participation Programme in the South African constitution-making process. The central premise of the thesis is that there is a link between participatory lawmaking processes and legitimate democracy. Accordingly, the drafting of the constitution and other law requires public participation in order to be accepted and recognised. Jurgen Habermas' latest theory (Between Facts and Norms) is used in this analysis. Jurgen Habermas has developed a new theoretical paradigm that defines the tension that exists between the coercive factual force of law ("facticity") and the recognition of law ("validity").